Assessing gender-responsive and nutrition-sensitive adaptation and mitigation actions using a national scorecard - Magalhaes, Marilia; Bryan, Elizabeth; Ringler, Claudia (International Food Policy Research Institute, 2023)
Women and men have different levels of exposure and sensitivity to climate change, given their different livelihood roles and other contextual factors. Moreover, given women’s relatively lower levels of adaptive capacity, they are often less likely to take up climate-smart practices in agri-food systems or influence decisions about which response options are chosen. These limitations contribute to differential well-being outcomes for men and women, such as nutritional status. They also reduce women’s potential contributions to increasing the climate resilience of food systems, and to meeting the greenhouse gas mitigation objectives of the agriculture sector. Despite growing evidence of these gender inequalities, few monitoring and evaluation frameworks have been developed to assess and monitor the gendered impacts of adaptation and mitigation interventions in the agricultural sector. The lack of reliable and timely metrics makes it harder to assess whether such interventions are effective in reducing gender inequalities, and meeting food security and nutrition objectives. The GCAN project is developing a national scorecard to support gender-responsive and nutritionsensitive monitoring of climate policies, investments and actions—informed by an extensive literature review, key informant interviews and stakeholder consultations. The scorecard is comprised of several domains reflective of policy decisions (e.g., level of gender integration in policy design), policy processes (e.g., women’s leadership and participation in policy design and implementation) and outcome indicators (e.g., women’s access to resources and services). The scorecard will be used to inform policy discussions about accountability toward the gender and nutrition objectives of climate actions.